Cystatin C kidney functional reserve: a simple method to predict outcome in chronic kidney disease. Issue 6 (27th May 2021) - Christiadi, Daniel; Simpson, Charles; O'brien, Kate; Taylor, Kylie; Luxton, Grant; Rossleigh, Monica; Erlich, Jonathan; Endre, Zoltán H
Abstract: Background: Kidney functional reserve (KFR), the only clinical kidney stress test, is not routinely measured because the complexity of measurement has limited clinical application. We investigated the utility of plasma cystatin C (CysC) after oral protein loading (PL) to determine KFR in Stages 3 and 4 chronic kidney disease (CKD). Methods: Following a 24-h low-protein diet, KFR was measured after oral protein by hourly plasma CysC and compared with simultaneous creatinine clearance (CrCl) and radionuclide 99 technetium diethylenetriaminepentaacetatic acid (Tc-99m-DTPA) measured glomerular filtration rate (mGFR) measurement in an observational, single-centre cohort study of adults with CKD Stages 3 and 4. Subjects were followed for 3 years for fast (F) or slow (S) CKD progression, dialysis requirement or death or a combination of major adverse kidney events (MAKEs). Result: CysC, CrCl and Tc-99m-DTPA mGFR measurements of KFR in 19 CKD Stage 3 and 21 CKD Stage 4 patients yielded good agreement. KFR was not correlated with baseline kidney function. Eight CKD Stage 3 (42%) and 11 CKD Stage 4 (52%) subjects reached their lowest serum CysC concentration 4 h after PL. CysC KFR and baseline serum creatinine (sCr) predicted death or dialysis or MAKE-F with a respective area under the curve (AUC)  of 0.73 [95% confidence interval (CI) 0.48–0.89] and 0.71 (95% CI 0.51–0.84). Including CysC KFR, age, baseline sCr and nadir CysC predicted a decrease in sCr-estimated GFR >1.2 mL/min/year (MAKE-S) with an AUC of 0.89. Conclusions: Serial CysC avoided timed urine collection and radionuclide exposure and yielded equivalent estimates of KFR. Serial CysC may facilitate monitoring of KFR in clinical practice. GRAPHICAL ABSTRACT: